Management of the effectiveness of investment planning using economic and mathematical modeling - Mykytyuk, Petro; Mykytyuk, Yuliia (Herald of Economics, 2023)
Introduction. When solving optimal tasks at the stage of technical and economic planning, it is necessary to establish an optimality criterion, which is mathematically written as an objective function. Minimization of the duration of the project works during its implementation within the time limit set by the investor is such a criterion in the formulation of our task. By limitations of the model, we understand such conditions, which are expressed in the limitation of resources both quantitatively and qualitatively: hence the problem of their saving, the best distribution, and effective use arises.Goal consists in the theoretical and methodological substantiation of the concept of managing the effectiveness of investment planning with the use of economic and mathematical modelingResearch methods. In the research process, general scientific and special methods of cognition were used: analysis and synthesis, theoretical generalization and formal logic, system approach, classification, statistical analysis, functional-value analysis, generalization, observation, mathematical statistics, simulation and network modeling, specification, technical and economic calculationsResults. It was found that with the help of the proposed technology «Flow» it is possible to determine: the calendar schedule of works for the optimal version of the project implementation; the calendar dates of the start and end of critical works, on which the duration of the entire project depends; actual project implementation costs. The value of the objective function shows what additional costs are necessary for the implementation of the investment project in a given period. It has been proven that the «Flow» technology allows you to determine the value of the model and, in our opinion, demonstrates the improvement of the existing solution to the tasks of project implementation within the given time and ensures the compatibility and unity of information support, and therefore allows you to receive more reliable data. The main advantages of the proposed method were evaluated: availability of raw data; a calculation algorithm that is understandable to any project participant; clarity of results; connection in a single model of the economic interests of the main participants of the project.Perspectives. Further research should be aimed at carrying out a continuous process of qualitative and quantitative assessment of the effectiveness of the project management information system and the need to create a special organizational unit - a strategic committee, which will allow the creation of mechanisms for effective management of investment projects of the territorial community, to achieve its strategic goals, and will also contribute to the implementation of strategies due to the consistent actions of the community investment development management staff.